Development of a finite element model of metal powder compaction process at elevated temperature - Rahman M.M.; Ariffin A.K.; Nor S.S.M. (2023)
This paper presents the finite element modelling of metal powder compaction process at elevated temperature. In the modelling, the behaviour of powder is assumed to be rate independent thermo-elastoplastic material where the material constitutive laws are derived based on a continuum mechanics approach. The deformation process of metal powder has been described by a large displacement based finite element formulation. The Elliptical Cap yield model has been used to represent the deformation behaviour of the powder mass during the compaction process. This yield model was tested and found to be appropriate to represent the compaction process. The staggered-incremental-iterative solution strategy has been established to solve the non-linearity in the systems of equations. Some numerical simulation results were validated through experimentation, where a good agreement was found between the numerical simulation results and the experimental data. 2009 Elsevier Inc. All rights reserved.